Collateral Ligament Prosthesis for Stabilization of Transverse Subchondral Fracture of Metatarsus III/IV in a Calf - Hirsbrunner, G.; Schawalder, P.; Steiner, A. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
The successful use of a collateral ligament prosthesis for stabilization of a transverse subchondral fracture of metatarsus III/IV in a newborn calf is reported. The proximal metaphysis of the right metatarsus III/IV was displaced medially with the medial collateral ligaments ruptured. On the medial side the periosteum was intact, whereas it was detached on the lateral side. The fracture was reduced and the collateral ligaments and the periosteum were reattached on the lateral side of the proximal metatarsus III/IV using titanium alloy staples. On the medial side a braided polypropylene yarn prosthesis, including the ruptured collateral ligaments was attached to the os tarsale II/III and the proximal metatarsus III/IV, using titanium alloy staples. The minimal internal stabilization was reinforced by a full limb fibreglass cast.Seven months after the operation clinical and radiographic follow-up examination revealed complete healing of the fracture without signs of ankylosis of the tarsometatarsal joint. The calf did not show any signs of lameness and axial alignment of the fractured bone in the frontal and sagittal plane was excellent.Subchondral fractures in calves have rarely been described. The case reported here deals with treatment of a subchondral fracture of metatarsus III/IV in a newborn calf. Open fracture reduction was followed by minimal internal stabilization, using a collateral ligament prosthesis, which was reinforced by external coaptation. Follow-up examination revealed complete healing of the fracture in good alignment.
Keywords: Calf; metatarsus III/IV; subchondral fracture; collateral ligament prosthesis